Is Korea's Public Funding for SMEs Achieving Its Intended Goals? - Woo Hyun Chang (Korea Development Institute (KDI), 2016)
Policies to support Small and Medium-sized Enterprises (SMEs) should be designed and managed in a way that SMEs are self-reliant and able to contribute to national economic goals. However, an evaluation of current public programs to support SME finance, an important policy instrument of Korea's SME support policy, shows that they have actually lowered the productivity of recipient firms and increased the survival probability of incompetent ones, negatively impacting the national economy. To produce the desired results, the government needs to (1) redefine the purpose of SME policy by shifting its emphasis from survival to productivity; (2) introduce a regular and scientific evaluation system by using appropriate performance indicators; and (3) restructure the policy to enhance efficiency based on evaluation results. - Scientific impact evaluations are the starting point for improving effectiveness of SME-support policies and their contribution to individual companies' performance and the national economy. Nevertheless, this principle is not sufficiently reflected in current policy evaluation practices. - This study evaluates the policy effectiveness of Korea's public funding for SMEs, which is one of the most important SMEsupport policies and maintains large and wellmanaged records. - As of 2014, public loans and guarantee balance of above 80 trillion won were provided by KODIT, KIBO and SBC. - This study collected the data on public funding for SMEs in 2009, which totaled about 60 trillion won. - This study used the data on mining and manufacturing companies with ten or more employees and linked it to public funding for SMEs records. This led to an evaluation of public funding for SMEs of about 19.6 trillion won. - The analysis of the impact of public funding for SMEs on firm productivity showed that recipients showed significantly lower productivity than nonrecipients. - The findings showed that public funding for SMEs in 2009 produced a potential loss in GDP of about 2.5 trillion won (in 2010 prices) in 2011 under an assumption that companies awarded public funding achieved a productivity increase to the same level as non-recipients. - Companies given public funding for SMEs in 2009 were 5.32%p more likely to survive than without public funding. - These results can be interpreted to be the negative consequences of government intervention. Market's efficiency enhancement will be hindered if underserving companies survive thanks to government intervention but fail to improve efficiency sufficiently. This will negatively impact overall economy's productivity. - The goal of SME-support policy should shift toward improved productivity, away from increasing survivability to improve the productivity of self-reliant SMEs by mitigating market failures. - Once policy goals are set right, the next step is to develop appropriate indicators to evaluate the performance of policy which can fully reflect the policy goals. Performance indicators should include fewer quantitative indicators—sales, employment and survival probability—and more of productivityrelated qualitative indicators—percapita valueadded and operational profit, which are more closely related to productivity. - Implementing agencies should perform targeting and execution in a way to improve these indicators. - A policy coordinating authority needs to review the evaluation results produced by a neutral evaluation agency on a regular basis in order to identify areas for improvement and ensure effective implementation.
Keywords: 330